Safety and feasibility of subarachnoid block in laparoscopic cholecystectomy - Mahmud Ekram Ullah; Md. Mushfiqur Rahman; Rajibul Haque Talukder; Refat Uddin Tareq; Md. Noor A Alam (IMC Journal of Medical Science, 2019)
Background and objectives: Laparoscopic surgery is normally performed under general anesthesia (GA), but regional techniques like epidural or subarachnoid block (SAB) have been found beneficial in patients having associated major medical problems. In selected cases, it can be a safe alternative to GA. Hence, the present study was conducted to explore the safety and feasibility of SAB in otherwise healthy individuals undergoing laparoscopic cholecystectomy.